Mengembangkan Modal Psikologis Siswa Sekolah Menengah Atas (SMA) Terbuka Sebelas November melalui Psikoedukasi - Sulistiyaningsih, Retno; Mubarok, Ali Syahidin; Andayani, Sri; Noorrizki, Rahkmaditya Dewi (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
This community service activity aims to improve the psychological capital of students at Sebelas November Open Senior High School (SMA Terbuka Sebelas November) through a psychoeducational program. The program's background stems from the challenges that emerged during the Covid-19 pandemic, when many students experienced a decline in learning motivation. Psychological capital is seen as a crucial aspect that every individual needs to be able to face various challenges more wisely. The community service process is carried out through three main stages: partner needs analysis, implementation of psychological capital intervention, and evaluation of results. In the core stage, students are provided with material on the concept of psychological capital and strategies for developing it in their daily lives. Furthermore, students are also involved in role-play activities that help them develop short-term and long-term plans related to their desired goals. To determine the effectiveness of the activity, pre- and post-tests were used to measure students' level of understanding of the material provided. The evaluation results showed a significant increase in knowledge after the psychological capital intervention compared to before the intervention. Thus, this program has been proven to have a positive impact in strengthening students' psychological capital, making them better prepared to face academic and non-academic challenges. Kegiatan pengabdian masyarakat ini dilaksanakan dengan tujuan meningkatkan modal psikologis siswa Sekolah Menengah Atas (SMA) Terbuka Sebelas November melalui program psikoedukasi. Latar belakang program berangkat dari permasalahan yang muncul selama pandemi Covid-19, ketika banyak siswa mengalami penurunan motivasi belajar. Modal psikologis dipandang sebagai aspek penting yang perlu dimiliki setiap individu agar mampu menghadapi berbagai tantangan dengan lebih bijaksana. Proses pengabdian dilakukan melalui tiga tahap utama, yaitu analisis kebutuhan mitra, pelaksanaan psychological capital intervention, serta evaluasi hasil. Pada tahap inti, siswa diberikan materi mengenai konsep modal psikologis serta strategi untuk mengembangkannya dalam kehidupan sehari-hari. Tidak hanya itu, siswa juga terlibat dalam kegiatan role play yang membantu mereka menyusun rencana jangka pendek maupun jangka panjang terkait cita-cita yang diharapkan. Untuk mengetahui efektivitas kegiatan, digunakan pre-test dan post-test guna mengukur tingkat pemahaman siswa terhadap materi yang diberikan. Hasil evaluasi menunjukkan adanya peningkatan pengetahuan yang signifikan setelah pelaksanaan psychological capital intervention dibandingkan dengan sebelum perlakuan dilakukan. Dengan demikian, program ini terbukti memberikan dampak positif dalam memperkuat modal psikologis siswa sehingga mereka lebih siap menghadapi tantangan akademik maupun non-akademik.